Fiscal Transfer Policies and Road Infrastructure Reduce Income Inequality in Rural-Urban Areas - Khusaini Khusaini; Bambang Mardisentosa; Tetuko Rawidyo Putro (ETIKONOMI, 2023)
Fiscal transfer policies and road infrastructure are essential in reducing inequality in Indonesia. However, previous research examining the effect of fiscal transfer policies and road infrastructure still came up with inconclusive findings, thus making it necessary to conduct further research on rural, urban, and sub-national areas in Indonesia. This study examines the impact of fiscal transfer policies and road infrastructure on reducing income inequality in rural, urban, and sub-national areas. The authors utilized time-series data from 2012 to 2021 and 34 provinces. The fixed effect GLS model showed that Kuznets' hypothesis existed at rural, urban, and sub-national levels. The results also showed that the special allocations fund significantly reduced income inequality in rural, urban, and sub-national areas. However, road infrastructure was significant only in urban areas. The findings suggest that the special allocation fund policy can be expanded in scope and increased in number to accelerate the reduction in income inequality.JEL Classification: O15, L92, O18, O23How to Cite:Khusaini, K., Sentosa, B. M., & Putro, T. R. (2023). Fiscal Policies and Road Infrastructure Reduce Income Inequality in Rural-Urban Areas. Etikonomi, 22(2), 333 – 356. https://doi.org/10.15408/etk.v22i2.28618.